THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND INTERPERSONAL COMMUNICATION ON THE ORGANIZATIONAL CULTURE OF TEACHERS AT THE BAYT INSAN MULIA FOUNDATION - Kultsum, Ummi (JURNAL ASIK, 2024)
The purpose of this study was to determine the influence of emotional intelligence and interpersonal communication on the organizational culture of teachers at the Bayt Insan Mulia Foundation. The research method used in this research is descriptive with a quantitative approach. The population was 35 people. The sampling technique using saturated samples so that the number of samples in this study was 35 respondents. Data analysis techniques using multiple regression. The results showed that: (1) There is a positive and significant effect of emotional intelligence variables on the organizational culture of teachers at the Bayt Insan Mulia Foundation with a tcount > ttable value, namely 4.732 > 1.689 and a significance value = 0.000 which is below 0.05. (2) There is a positive and significant effect of interpersonal communication variables on the organizational culture of teachers at the Bayt Insan Mulia Foundation with a tcount> ttable value, namely 7.268 > 1.689 and a significance value = 0.000, which is below 0.05. (3) There is a positive and significant influence of emotional intelligence and interpersonal communication on the organizational culture of teachers at the Bayt Insan Mulia Foundation with the value of Fcount > Ftable value, namely 27.262 > 3.27 and significance value = 0.000 which is below 0.05.